History of Education, History of Health and Disease. Parallel paths? For an inter/multidisciplinary history - Perdiguero-Gil, Enrique; del Cura Gonz´ález, Mercedes (Historia y Memoria de la Educación, 2021)
Introduction to the special Issue Education and Health: Intersections, Disagreements and Synergies in the Second Half of the tweentieth Century